Examination of BDNF Treatment on BACE1 Activity and Acute Exercise on Brain BDNF Signaling - Baranowski, Bradley J.; Hayward, Grant C.; Marko, Daniel M.; MacPherson, Rebecca E. K. (Frontiers in Cellular Neuroscience, 2021)
Perturbations in metabolism results in the accumulation of beta-amyloid peptides, which is a pathological feature of Alzheimer’s Disease. Beta-site amyloid precursor protein cleaving enzyme 1 (BACE1) is the rate limiting enzyme responsible for beta-amyloid production. Obesogenic diets increase BACE1 while exercise reduces BACE1 activity, although the mechanisms are unknown. Brain-derived neurotropic factor (BDNF) is an exercise inducible neurotrophic factor however it is unknown if BDNF is related to the effects of exercise on BACE1. The purpose of this study was to determine the direct effect of BDNF on BACE1 activity and to examine neuronal pathways induced by exercise. C57BL/6J male mice were assigned to either a low (n=36) or high fat diet (n=36) for 10 weeks. To determine the direct effect of BDNF on BACE1, a subset of mice (low fat diet =12 and high fat diet n=12) were used for an explant experiment where the brain tissue was directly treated with BDNF (100ng/ml) for 30 min. To examine neuronal pathways activated with exercise, mice remained sedentary (n=12) or underwent an acute bout of treadmill running at 15 m/min with a 5% incline for 120 minutes (n=12). The prefrontal cortex and hippocampus were collected 2-hours post-exercise. Direct treatment with BDNF resulted in reductions in BACE1 activity in the prefrontal cortex (p<0.05), but not the hippocampus. The high fat diet reduced BDNF content in the hippocampus; however, the acute bout of exercise increased BDNF in the prefrontal cortex (p<0.05). These novel findings demonstrate the region specific differences in exercise induced BDNF in lean and obese mice and show that BDNF can reduce BACE1 activity, independent of other exercise-induced alterations. This work demonstrates a previously unknown link between BDNF and BACE1 regulation.